Impact of aging vs. estrogen loss on cardiac gene expression: estrogen replacement and inflammation - Pechenino, Angela S. (American Physiological Society, 2011)
Despite an abundance of evidence to the contrary from animal studies, large clinical trials on humans have shown that estrogen administered to postmenopausal women increases the risk of cardiovascular disease. However, timing may be everything, as estrogen is often administered immediately after ovariectomy (Ovx) in animal studies, while estrogen administration in human studies occurred many years postmenopause. This study investigates the discrepancy by administering 17β-estradiol (E2) in a slow-release capsule to Norway Brown rats both immediately following Ovx and 9 wk post-Ovx (Late), and studying differences in gene expression between these two groups compared with age-matched Ovx and sham-operated animals. Two different types of microarray were used to analyze the left ventricles from these groups: an Affymetrix array (n = 3/group) and an inflammatory cytokines and receptors PCR array (n = 4/group). Key genes were analyzed by Western blotting. Ovx without replacement led to an increase in caspase 3, caspase 9, calpain 2, matrix metalloproteinase (MMP)9, and TNF-α. Caspase 6, STAT3, and CD11b increased in the Late group, while tissue inhibitor of metalloproteinase 2, MMP14, and collagen I α1 were decreased. MADD and fibronectin were increased in both Ovx and Late. TNF-α and inducible nitric oxide synthase (iNOS) protein levels increased with Late replacement. Many of these changes were prevented by early E2 replacement. These findings suggest that increased expression of inflammatory genes, such as TNF-α and iNOS, may be involved in some of the deleterious effects of delayed E2 administration seen in human studies.